Inside the Hidden Curriculum: “How-To” Practices for Supporting Underprepared Student Writers in the First-Year Writing Classroom - Starkowski, Kristen (Discourse and Writing/Rédactologie, 2022)
First-year writing pedagogies prioritize encouraging students to forge an academic identity by conceptualizing and intervening in scholarly conversations. Student writers from institutionally underprepared backgrounds often find this process both limiting and empowering because specific practices associated with classroom expectations and the university experience remain unfamiliar to them. In this article, I reveal a need for “how-to” exercises within the first-year writing classroom that aim to dismantle the hidden curriculum—a term that denotes the resources, norms, and values that are inaccessible to students who have not received guidance on these aspects of university academics. These interventions, which range from instruction on modes of classroom participation to methods of preparing for office hours, already complement the standard first-year writing curriculum and promise to promote success among underprepared students by rendering possibilities for class engagement explicit.